Hubungan antara Pemahaman Konsep dengan Beban Kognitif Siswa pada Materi Hidrolisis Garam - Sabilla, Zahara; Ridwan, Achmad; Yusmaniar, Yusmaniar (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
This purpose of this study is to determine the relationship between cognitive load and understanding students' concepts in salt hydrolysis material. The subjects were 96 students of class XI MIA 1, XI MIA 6 and XI MIA 7 at SMAN 2 Cibinong. Research conducted based on the problem of a person's ability to receive and process information that exceeds the required memory capacity will increase cognitive load. The method used in this study is descriptive correlational. The results of the hypothesis with Spearman Rank obtained a significant negative relationship for salt hydrolysis material, so it can be concluded that low cognitive load will generate a high understanding of concepts. Keywords: Cognitive load, concept understanding, hydrolysis of the salt